2019
DOI: 10.1051/0004-6361/201833545
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields of intermediate-mass T Tauri stars

Abstract: Context. The origin of the fossil magnetic fields detected in 5 to 10% of intermediate-mass main sequence stars is still highly debated. Aims. We want to bring observational constraints to a large population of intermediate-mass pre-main sequence (PMS) stars in order to test the theory that convective-dynamo fields generated during the PMS phases of stellar evolution can occasionally relax into fossil fields on the main sequence. Methods. Using distance estimations, photometric measurements, and spectropolarim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 76 publications
10
76
0
Order By: Relevance
“…Muzerolle et al (2004) showed that the MA models provided qualitative agreement with the observed emission line profiles of the Herbig Ae star UX Ori. In the process, they also found that the B-field geometry should be more complex than the usual dipole field in T Tauri stars and the expected field strength would be much below the usual T Tauri detections, in line with the Villebrun et al (2019) findings.…”
Section: Discussionsupporting
confidence: 58%
“…Muzerolle et al (2004) showed that the MA models provided qualitative agreement with the observed emission line profiles of the Herbig Ae star UX Ori. In the process, they also found that the B-field geometry should be more complex than the usual dipole field in T Tauri stars and the expected field strength would be much below the usual T Tauri detections, in line with the Villebrun et al (2019) findings.…”
Section: Discussionsupporting
confidence: 58%
“…One prediction of a bistability scenario is that magnetic fields should be ubiquitous during the earliest phases of the PMS, when the star is at least partially convective, and should rapidly disappear once stars become radiative. This is precisely what was found by Villebrun et al (2019) in their study of intermediate mass T Tauri stars (IMTTS). They showed that essentially all IMTTS with convective envelopes are magnetic, while very few of the fully radiative IMTTS host magnetic fields.…”
Section: Discussionsupporting
confidence: 87%
“…(i) Magnetization of the protostellar cloud provides the seed for the fossil field, and also inhibits fragmentation of the cloud and therefore prevents the formation of binaries (Commerçon et al 2011) (ii) Fossil fields are left over from dynamos powered by stellar mergers (Schneider et al 2016) (iii) Tidal interactions in eccentric binaries lead to the rapid decay of fossil magnetic fields (Vidal et al 2019) The existence of some, rather than no, close binaries including at least one star with a fossil field suggests that i) is unlikely to be universally true. This depends on whether magnetization prevents fragmentation, or simply makes it unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We perform the radiative transfer calculation to derive the temperature distributions in the disk r − z plane when the dust disk is more compact than the gas disk by using a published code HO-CHUNK (Whitney et al 2003a(Whitney et al ,b, 2004(Whitney et al , 2013. We adopt the stellar mass of 1.657 M ⊙ , the effective temperature of 4800 K, and the stellar radius of 3.113 R ⊙ (Villebrun et al 2019). We also use the dust surface density derived from the observed I cont at T dust = T B,peak, 13 CO .…”
Section: Dust Concentration On the Gas Pressure Bumpmentioning
confidence: 99%